Rationale and study design for a randomised controlled trial to reduce sedentary time in adults at risk of type 2 diabetes mellitus: project stand (Sedentary Time ANd diabetes) - Wilmot Emma G; Davies Melanie J; Edwardson Charlotte L; Gorely Trish; Khunti Kamlesh; Nimmo Myra; Yates Thomas; Biddle Stuart JH (BMC, 2011)
Abstract Background The rising prevalence of Type 2 Diabetes Mellitus (T2DM) is a major public health problem. There is an urgent need for effective lifestyle interventions to prevent the development of T2DM. Sedentary behaviour (sitting time) has recently been identified as a risk factor for diabetes, often independent of the time spent in moderate-to-vigorous physical activity. Project STAND (Sedentary Time ANd Diabetes) is a study which aims to reduce sedentary behaviour in younger adults at high risk of T2DM. Methods/Design A reduction in sedentary time is targeted using theory driven group structured education. The STAND programme is subject to piloting and process evaluation in line with the MRC framework for complex interventions. Participants are encouraged to self-monitor and self-regulate their behaviour. The intervention is being assessed in a randomised controlled trial with 12 month follow up. Inclusion criteria are a) aged 18-40 years with a BMI in the obese range; b) 18-40 years with a BMI in the overweight range plus an additional risk factor for T2DM. Participants are randomised to the intervention (n = 89) or control (n = 89) arm. The primary outcome is a reduction in sedentary behaviour at 12 months as measured by an accelerometer (count < 100/min). Secondary outcomes include physical activity, sitting/lying time using the ActivPAL posture monitor, fasting and 2 h oral glucose tolerance test, lipids, inflammatory biomarkers, body weight, waist circumference, blood pressure, illness perceptions, and efficacy beliefs for behaviour change. Conclusions This is the first UK trial to address sedentary behaviour change in a population of younger adults at risk of T2DM. The results will provide a platform for the development of a range of future multidisciplinary interventions in this rapidly expanding high-risk population. Trial registration Current controlled trials ISRCTN08434554, MRC project 91409.